Phase Changes and Photocatalytic Activity of BIMNVOX Series for Degradation of Crystal Violet Dye in Aqueous Medium under Visible Light Irradiation - Ahlam Al–Alas; Niyazi A. S. Al–Areqi; Raya Qaid Alansi (Enhanced Knowledge in Sciences and Technology, 2022)
A layered Aurivillius–perovskite type BIMNVOX compound with a general formula, was developed as an effective photocatalyst for degradation of organic dyes. A series of BIMNVOX.x catalysts in the composition range 0 ≤ x ≤ 0.20 were successfully prepared using the standard solid– state reaction and characterized using X–ray diffraction (XRD), differential thermal analysis (DTA), UV–vis spectrophotmetry and adsorption measurements. Then, the photocatalytic activities of synthesized catalysts were investigated for the first time through the photodegradation of crystal violet, CV dye in aqueous solution under visible light irradiation. Adsorption efficiency and photocatalytic activity of BIMNVOX.x catalysts were correlated well with the variation in phase crystal structures stabilized at room temperature as a function of composition. The stabilized β–BIMNVOX phase in the orthorhombic crystal system, space group Acam exhibited the best photocatalytic performance, though broadening band– gap energy. This can be attributed to their higher specific surface area, higher oxygen –vacancy concentration in the perovskite vanadate layers. In addition, the possible photocatalytic degradation mechanism of aqueous CV dye was clearly proposed.